Student Perception Regarding Efficacy of Online Vs Traditional Campus-Based Teaching and Challenges - Hira Butt, Maham Qasim, Samra Liaqat, Aqsa, Zainab Waheed, Khadija Amjad (Pakistan Journal of Medical & Health Sciences, 2022)
To analyze the student`s perception of the effectiveness of online versus campus-based teaching. A descriptive cross-sectional study was conducted on students of Bachelor of Dental Surgery from College of Dentistry, Sharif Medical and Dental College Lahore. Dental students from all four years were included in the study irrespective of their academic records. Students who did not attend the online classes or refused to give consent were excluded from the study sample. A pre-validated questionnaire with a Cronbach alpha of 0.94 was used. The difference in the mean rank score across different student perceptions of the effectiveness of online in comparison to campus-based teaching was significant for motivational problems and time interruptions (p≤0.001) while non-significant for instructor and personal problems (p=0.437), lack of support services (p=0.942), lack of pre-requisite skills (p=0.218), technical problems (p=0.238) and lack of social interaction (p=0.187). The difference in the motivational problems and time interruptions across the different student perceptions was significant with the highest mean rank score for students who cannot learn well in online classes as in traditional classes. Keywords: Online learning, campus-based learning, student perception, effectiveness